Burned and unburned section 26 in spring - Sprague, Sallie, photographer (Colorado State University. Libraries, 2008)
Comparison of green vegetation in burned and brown in unburned areas of section 26, with cattle in distance.
Keywords: vegetation; SGS; experiments; landscapes